Cloning and Expression of a Subfamily 1.4 Lipase from Bacillus licheniformis IBRL-CHS2 - Nidyaletchmy Subba Reddy; Rashidah Abdul Rahim; Darah Ibrahim; K. Sudesh Kumar (Tropical Life Sciences Research, 2016)
We report on the cloning of the lipase gene from Bacillus licheniformis IBRL-CHS2 and the expression of the recombinant lipase. DNA sequencing analysis of the cloned lipase gene showed that it shares 99% identity with the lipase gene from B. licheniformis ATCC 14580 and belongs to subfamily 1.4 of true lipases based on amino acid sequence alignment of various Bacillus lipases. The 612 bp lipase gene was then cloned into the pET-15b(+) expression vector and the construct was transformed into E. coli BL21 (DE3) for bulk expression of the lipase. Expression was analysed by SDS-PAGE where the lipase was found to have a molecular weight of about 23 kDa.